THE EFFECTIVITY OF CUTTING TECHNIQUE FOR VIABILITY PROPAGULE OF Rhizophora stylosa - Asihing Kustanti (JOURNAL OF COASTAL DEVELOPMENT, 2005)
The aim of this research was to investigate the viability afRhiz0ph0ra stylosa propagule due to cutting · treatments (I/3 and 2/3) The result of this research showed that R. stylasa without and I/3 cutting of propagule gave the best result. The viability, i.e. germination ability, rapid growth value, and germination value was the higher compared to the other treatments.